The Impact of Artificial Intelligence on Digital Marketing: Leveraging Potential in a Competitive Business Landscape - Hendrayati, Heny; Achyarsyah, Mochamad; Marimon, Frederic; Hartono, Ulil; Putit, Lennora (Emerging Science Journal, 2024)
This study aims to thoroughly investigate how Artificial Intelligence (AI) is strategically integrated into digital marketing practices and its consequential effects on Indonesia’s fiercely competitive business environment. Employing a quantitative research approach, this study meticulously examines Indonesian enterprises’ prevailing strategies for AI utilization. The research method employed in this study is quantitative, with the unit of analysis being Indonesian companies. The sample size comprises 100 companies selected through the stratified random sampling technique. Analysis of the data is conducted using the SPSS statistical package. Through detailed analysis of survey data and advanced statistical techniques, the research reveals a significant positive correlation between the integration of AI in digital marketing and improved marketing effectiveness. The study highlights a noticeable increase in customer engagement metrics and noteworthy enhancements in conversion rates among businesses proficient in leveraging AI technologies, further reinforcing this correlation. Additionally, the findings suggest that companies embracing AI demonstrate significantly heightened adaptability to the constantly evolving market dynamics, strengthening their competitive positioning. These insightful discoveries underscore the critical importance of harnessing AI’s transformative capabilities within digital marketing strategies to sustain and bolster a competitive edge in the marketplace. Furthermore, the study discusses its contributions to existing knowledge and provides practical implications for marketers and business policymakers in Indonesia. Doi: 10.28991/ESJ-2024-08-06-012 Full Text: PDF